Multigram-scale synthesis of l, d-heptoside using a Fleming-Tamao oxidation promoted by mercuric trifluoroacetate. (2nd September 2016) - Li, Tianlei; Tikad, Abdellatif; Durka, Maxime; Pan, Weidong; Vincent, Stéphane P.
Abstract: An efficient multigram-scale synthesis of methyl 2, 3, 4, 6-tetra- O -benzyl-l - glycero -α-d - manno -heptopyranoside from methyl 2, 3, 4-tri- O -benzyl-α-d -mannopyranoside is reported. It involves a sequence of Swern oxidation, Grignard addition and Fleming-Tamao reactions. The resulting scaffold was used as a precursor to design a small library of clickablel -heptosides. This study shows that the use of mercuric bistrifluoroacetate is required both to accelerate and to cleanly perform the Fleming-Tamao oxidation, without side-reactions. Graphical abstract: Highlights: Heptosides are important bacterial carbohydrates associated with key cellular functions. Heptosides are involved in the pathogenicity and the virulence of some important infectious agents. Multi-gram scale synthesis of L, D-mannoheptose, a key component of Lipopolysaccharide. Clickable heptosides as interesting molecular tools for generating libraries of heptose mimetics. Heptose glycomimetics.